Factors Associated with the Nutritional Status of Children Aged 3 - 5 Years at Hasanuddin Mandai Community Health Center, Mandai District, Maros Regency - Nurbaiti, Nurbaiti (Jurnal Perilaku Kesehatan Terpadu, 2022)
Nutritional problems are essentially a public health problem, but overcoming them cannot be done with a medical approach and health services alone. The causes of nutritional problems are multifactorial, therefore the approach to overcoming them must involve various related sectors. Based on data from the South Sulawesi Health Service in 2005, there were 14,650 (3.45%) children under five who were malnourished. Meanwhile, in the city of Maros, there were 463 (2.40%) children under five who were malnourished, and in particular at the Hasanuddin Mandai Community Health Center in 2006 there were 35 (10.17%) children aged 3 - 5 years who were malnourished. This study aims to determine the factors related to the nutritional status of children aged 3 - 5 years at the Hasanuddin Mandai Community Health Center, Mandai District, Maros Regency. The research design used in this research is analytical descriptive using the "Cross Sectional Study" approach method. The sample in this study was 77 children aged 3 - 5 years who were at the location at the time of the research using the Purposive Sample technique . The way to collect data is by taking measurements of the child's weight, then making observations and distributing questionnaires to respondents. To determine the factors related to the nutritional status of children aged 3 - 5 years, the Pearson Chi Square Test was used with a significance level of ? = 0.05 in SPSS version 12. The results of the study showed that there was a significant relationship between the factors of children's diet and mother's knowledge. , maternal occupation and parenting patterns with children's nutritional status, but there is an insignificant relationship between maternal education and family income and nutritional status of children aged 3 - 5 years at the Hasanuddin Mandai Community Health Center, Mandai District, Maros Regency.